Diseño de la planeación estratégica de la empresa Montajes y Eventos S.A.S. (2021)
Through this study that covers the strategic planning of the company Montajes y Eventos, a diagnosis was made that would allow the analysis of internal and external factors that the company has. For the external analysis, the PEST strategy was used, taking into account political, economic, sociocultural and technological factors where it is evident how these significantly influence the economic development of the company. To analyze the internal factors, the self-diagnosis tool of the Bogotá Chamber of Commerce is considered, which shows commercial, operational, administrative, financial aspects, among others where the weaknesses and strengths that the company presents can be identified through a result at the moment. On the other hand, the SWOT matrix was implemented in order to establish weaknesses, opportunities and threats that serve to carry out strategies for the improvement of the company. Indeed, due to the different factors analyzed, the implementation of strategic planning can be carried out to lead the company to a more prosperous future.